2020
DOI: 10.1021/acs.cgd.9b01681
|View full text |Cite
|
Sign up to set email alerts
|

Short and Linear Intermolecular Tetrel Bonds to Tin. Cocrystal Engineering with Triphenyltin Chloride

Abstract: Group 14 (tetrel) elements potentially provide a region of low electronic density (σ-hole) and elevated electrostatic potential, which acts as an electrophilic site to form attractive interactions with electron-rich moieties. Tetrel bonds are the result of net attractive interaction between an electrophilic region associated with a tetrel atom in a molecular entity and a nucleophilic region in another, or the same, molecular entity. Here, we describe a systematic study of the potential utility of tetrel bonds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…The anisotropic distribution of electron density at the outer regions of bonded atoms was first used to rationalize the noncovalent interactions formed by these atoms in the early 1990s [1] . This approach is now successfully used to explain the interactions of all groups of p‐block elements in the periodic table [2] and provides valuable contributions to many fields, including catalysis, [3] drug design, [4] and crystal engineering [5] . Seven years ago, a possible extension of this mindset to d‐block elements was considered [6] and subsequently confirmed, first for elements of Group 11, [7] and then for elements of Groups 10 [8] and 12 [9] .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The anisotropic distribution of electron density at the outer regions of bonded atoms was first used to rationalize the noncovalent interactions formed by these atoms in the early 1990s [1] . This approach is now successfully used to explain the interactions of all groups of p‐block elements in the periodic table [2] and provides valuable contributions to many fields, including catalysis, [3] drug design, [4] and crystal engineering [5] . Seven years ago, a possible extension of this mindset to d‐block elements was considered [6] and subsequently confirmed, first for elements of Group 11, [7] and then for elements of Groups 10 [8] and 12 [9] .…”
Section: Figurementioning
confidence: 99%
“…[1] This approach is now successfully used to explain the interactions of all groups of p-block elements in the periodic table [2] and provides valuable contributions to many fields, including catalysis, [3] drug design, [4] and crystal engineering. [5] Seven years ago, a possible extension of this mindset to dblock elements was considered [6] and subsequently confirmed, first for elements of Group 11, [7] and then for elements of Groups 10 [8] and 12. [9] Various theoretical studies, [10][11][12][13] and a more limited number of experimental findings, [14,15] have shown that nanoparticles [16] and halide salts [14] of Cu, Ag, and Au form attractive interactions with a variety of donors of electron density by involving the regions with the most positive electrostatic potential at their outer surface.…”
mentioning
confidence: 94%
“…There have been numerous reports that the tetrel bond (TB) represents an important stabilization motif in a plethora of crystalline solids [3f,10] . As prominent examples, the appearance of tin and lead as building blocks for MOF's and other supramolecular synthons [10d] or the common layout of the germanium/tin nucleophile site interactions [10m,p] offer a good deal of promise for future development. The tetrel bond was also recently studied with regard to its contribution to anion recognition activity [11] and competition or cooperation with such other noncovalent interactions as hydrogen or halogen bonds [8c,12] .…”
Section: Introductionmentioning
confidence: 99%
“…CdHal 2 ÁPyNO with Hal = Cl (Beyeh & Puttreddy, 2015), Hal = I (Sawitzki & von Schnering, 1974), CuCl 2 Á2MePyNO (Johnson & Watson, 1971), Ni(BF 4 ) 2 Á6PyNO (Ingen Schenau et al, 1974), Au(CF 3 ) 3 ÁPyNO (Pé rez-Bitriá n et al, 2017), MoO(O 2 ) 2 Á-2MePyNO (Griffith et al, 1994)] as well as of p-block metals [i.e. TlBr 3 ÁPyNO (Bermejo et al, 1991); TlBr 3 Á2PyNO (Hiller et al, 1988); TlBrI 2 ÁMePyNO (Hiller et al, 1988); SnI 4 Á2PyNO (Wlaźlak et al, 2016), Me 2 SnCl 2 Á2PyNO (Blom et al, 1969), Ph 3 SnClÁPyNO (Kumar et al, 2020). With the exception of SbF 3 ÁPyNO (Benjamin et al, 2012) and BiI 3 ÁPyNO (Wlaźlak et al, 2020), no complexes of low-valent post-transition-metal elements have been crystallographically determined so far.…”
Section: Chemical Contextmentioning
confidence: 99%